Mengembangkan Aktivitas, Motivasi Dan Aspek Bahasa Anak Dalam Menyebutkan Simbol Huruf Melalui Model PBL, MAM, DAN TK - Mawaddaturrahmah; Aslamiah (Jurnal Pendidikan Sosial Dan Konseling, 2025)
The problem in this study is the low activity, motivation, and results of children's language development in mentioning letter symbols. The cause of this problem is the lack of active involvement of children in the learning process because learning is one-way, learning is less interesting, learning is abstract, and learning is less varied. The solutions provided are through the problem based learning model, make a match, and guess the word. The purpose of this study is to describe teacher activities, and analyze the increase in children's activities, learning motivation, and the results of the development of language aspects in mentioning letter symbols.This research approach uses qualitative with the type of PTK. The research was conducted in Group B of TK Negeri Tamban, involving 12 children as participants. The results of the study showed that Teacher Activities increased until meeting 4 reached a score of 23. Children's Activity increased until meeting 4 reached a percentage of 100%. Children's Learning Motivation increased until meeting 4 to 100%. The results of Children's Language Development in Mentioning Letter Symbols increased at every meeting until meeting 4 reaching 100%. This study can serve as input for teacher training, as an alternative learning model, and as a reference for future research.